As representações da cultura do estupro e da violência de gênero a partir do cinema de Karim Aïnouz: uma análise dos filmes “O céu Suely” e “A vida invisível” - Mendonça, Fernanda Perez (2021)
This research presents an analysis of the representations of the rape culture and gender violence from the films (registered culture) of the Brazilian filmmaker Karim Aïnouz, specifically “O céu de Suely” (2006) and “A vida invisível” (2019), in order to understand how these representations, thought from the hegemonic patriarchal norms, dialogue with the context of production of the study objects (lived culture). It is also intended to problematize the violent behaviors, mainly, the masculine ones, that occur in the bosom of a patriarchal, sexist and misogynist society, that tries to keep the woman under control of the gender standards, relegating to the feminine specific and unequal places as related to freedoms, rights and security. For this, this study explores the origins, motivations and trajectory of the rape culture and the practices of gender violence, from a historical and conceptual survey, and from the exploration of the social context that permeates this scenario. The theoretical foundation is based on Cultural Studies and concepts such as representation, gender, culture and hegemony. The methodology used is based on cultural-media analysis and on some precepts of film analysis. The obtained results demonstrate that, in general, the representations of the rape culture and gender violence, present in the registered culture, dialogue in a reliable way with the experienced culture, identified through the investigation of the historical, social and political context from the 1950s and nowadays, from a perspective of power and gender relations.